2019
DOI: 10.1111/mbe.12223
|View full text |Cite
|
Sign up to set email alerts
|

“UNIFIED”: Bridging the Researcher–Practitioner Divide in Mind, Brain, and Education

Abstract: Mind, Brain, and Education (MBE) science is by definition transdisciplinary. However, the communication and collaboration between constituent disciplines needed for true transdisciplinarity remains relatively rare. Consequently, many of the potential benefits of MBE science remain unrealized for parties on all sides of the discipline. The present commentary first conducts an analysis of the current strengths, weaknesses, opportunities, and threats of transdisciplinary partnerships in MBE. A new, free, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
0
16
0
3
Order By: Relevance
“…The development of the Open Schools Self-Reflection Tool (OSOS-SRT) was the response to follow the organisational change during the implementation. Based on the recent methodologies for assessing the impact of RRI in education (Hobbiss et al, 2019;van Atteveldt et al, 2019), it analysed the school community engagement in research and innovation. Furthermore, it is supposed to enable easier access to scientific results for students, to take up gender and ethics in the research and innovation content and process, and to act as a bridge of formal and informal science education, on the EU recommendations for the science education and on the development of responsible citizenship (EC, 2015a) as well as to analyse schools' e-maturity (Kampylis et al, 2015;Sotiriou et al, 2016;EC, 2019b).…”
Section: Methods Of Assessing the Effectiveness Of The Open Schooling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the Open Schools Self-Reflection Tool (OSOS-SRT) was the response to follow the organisational change during the implementation. Based on the recent methodologies for assessing the impact of RRI in education (Hobbiss et al, 2019;van Atteveldt et al, 2019), it analysed the school community engagement in research and innovation. Furthermore, it is supposed to enable easier access to scientific results for students, to take up gender and ethics in the research and innovation content and process, and to act as a bridge of formal and informal science education, on the EU recommendations for the science education and on the development of responsible citizenship (EC, 2015a) as well as to analyse schools' e-maturity (Kampylis et al, 2015;Sotiriou et al, 2016;EC, 2019b).…”
Section: Methods Of Assessing the Effectiveness Of The Open Schooling Approachmentioning
confidence: 99%
“…• Management: The aim of the instrument is to assess the vision, the leadership of the school community key stakeholders towards the adoption of a changing culture towards openness (Earley and Greany, 2017;Hobbiss et al, 2019), and the overall innovation potential of the school community (George and Desmidt, 2018) and to highlight the appearance (or not) of the key factors that can catalyse the cultural changes (e.g., coherence of local or national policies, development of a shared vision and understanding, development of motivation mechanisms and specific plans for staff competencies, school autonomy). This section of the instrument includes a step-by-step approach for the school heads to define a root of development and to locate the current position of their school in the innovation journey.…”
Section: Methods Of Assessing the Effectiveness Of The Open Schooling Approachmentioning
confidence: 99%
“…Another promising approach to increasing the ecological validity of research for educational practice—one that aligns with the transdisciplinary goals of multidisciplinary fields such as the SoL—involves stronger engagement with stakeholders and a bidirectional approach to research—for a move away from research being done “to” educators to research being done “with” and “by” educators in partnership with researchers (Farley‐Ripple et al, 2018; Hobbiss et al, 2019; Levin, 2013; van Atteveldt et al, 2018). Rather than the traditional one‐way direction of research to practice, a bidirectional reciprocal partnership could assist in addressing challenges of translation relating to knowledge production and use.…”
Section: Levin's Frameworkmentioning
confidence: 99%
“…Second, the transformation of research into usable knowledge for practice has been shown to benefit from the support of knowledge brokers. Effective knowledge brokers can support educators to build research capabilities as well as their understanding of the research evidence, and work with them to co‐construct contextually relevant applications (Brown, 2020; Cooper et al, 2020; Farley‐Ripple, 2017; Gorard et al, 2020; Hobbiss et al, 2019; Neal et al, 2015). Involving educators in the design, implementation, and evaluation of research in their own context can also assist in preventing the misinterpretation of research findings when translated into the classroom context (Howard‐Jones, 2014).…”
Section: Levin's Frameworkmentioning
confidence: 99%
See 1 more Smart Citation